The phenomenon of intellectual nature - B. B. Leontjev (Библиосфера, 2014)
A description of a new concept - the phenomenon of intellectual nature as one of the most large-scale and complex for science natural phenomena, understanding of which may start a new era in the development of science, economics, policy and civilization, is given. The consequences of its introduction into scientific use are predicted. The chances of Russia to become a world leader in this direction and efficiently develop social, technical and fundamental scientific knowledge are estimated.